PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MENGGUNAKAN MODEL GUIDED DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI HUKUM NEWTON - Nanda Annisa Solikhah; Riki Perdana (Universitas Tanjungpura, 2023)
The analysis of students' understanding of concepts in physics learning is still low. So that learning tools are needed that can improve students' understanding of concepts. This research aims to develop physics learning tools with a guided discovery learning model on the subject of Newton's laws to improve the understanding of students' concepts. The research and development method uses a 4D model consisting of 4 stages, namely (1) define (analysis of learning needs), (2) design (product design), (3) develop (feasibility test or product validation), and (4) dessiminate (dissemination of the final product). Product validation or feasibility testers are carried out by 1 expert lecturer in the field of Physics Education and 3 students who are studying in the field of Physics Education. The results obtained in the feasibility test of the learning device developed showed that the average percentage value in rpp eligibility was obtained 89.5%, in LKPD it was 87.5%, and the average percentage value in the concept understanding assessment instrument had a value of 94%. Based on the results of the analysis obtained, physics learning tools with a guided discovery learning model on the subject matter of Newton's laws which to improve the understanding of students' concepts are included in the very feasible category.